PLAGIARISME DETECTION SYSTEM ON THIEF FACULTY OF COMPUTER SCIENCE UNIVERSITY U'BUDIYAH INDONESIA BASED TEXT MINING - TB, Desita Ria Yusian; Fathiah, Fathiah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2016)
Plagiarism is the act of intentionally or unintentionally in obtaining ortrying to obtain credit or value to scientific work., citing part or all of thework / or scientific work of others who are recognized as scientific works,co without stating the source appropriately and adequately. Problem ofplagiarism has become a phenomenom that is being discussed inacademic forums. Based on a variety of information about the practice ofplagiarism is increasingly disturbing, this study conducted at the UbudiyahUniversity Indonesia (UUI). This system will implemented the detectionsystem plagiarism that will be creating using a document apllied method ofvector space model to analyze similarities in document displayed on theweb browser. Input on this system is a document in the form of text formatwhith the extention test performed on real data that is usig data documentswith vector space model algorithm value is above 85% to 100% for highlevel document. As for a document with a low degree of similarity valuesbelow 50%.Keyword : Plagiarism, Vector Space Model, Similarity